COVID-19 and the Energy Crisis: Saudi Arabia's Diplomatic Steps Through OPEC Negotiations - Rusniyanti, Rusniyanti; Mayllian, Veronica Patricia; Putri, Angelina Aprilia; Sahide, Ahmad (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
The COVID-19 pandemic significantly impacted global economic growth, including the energy sector, due to the drastic drop in world oil prices. Saudi Arabia, as a key player in OPEC (Organization of the Petroleum Exporting Countries), uses diplomacy to maintain the stability of the oil market. This research aims to understand Saudi Arabia's energy diplomacy in the face of the instability of the global commodity market caused by the pandemic. The theory used in this research was energy diplomacy, which examines Saudi Arabia's strategy as a key player in OPEC with other oil-producing countries. This study used a qualitative descriptive method with secondary data from relevant literature on Saudi energy policy and diplomacy during the COVID-19 pandemic. This study found that, first, Saudi Arabia successfully used its position in OPEC to achieve a consensus on oil production cuts during the COVID-19 pandemic and collaborated with non-OPEC countries to stabilize global oil prices. This strategy strengthens Saudi diplomacy's ability to address the challenges of the crisis, using energy diplomacy as a tool to handle the crisis and maintain national economic stability.